Ethnic differences in psychosis—Lay epidemiology explanations. (30th April 2019) - Schofield, Peter; Kordowicz, Maria; Pennycooke, Earl; Armstrong, David
Abstract: Background: Much research attention has been given to the high rates of psychosis diagnosed in the Black community. However, little has been heard about possible reasons for this from Black African and Caribbean mental health service users themselves. Aims: To determine how Black African and Caribbean service users perceive and explain these apparent differences. Methods: We conducted four focus groups between 2014 and 2015 with 35 participants from the Black African and Black Caribbean community in Lambeth and Southwark, South East London, diagnosed with a psychotic illness. Recruitment was through a local voluntary sector organization and other community contacts. Results: Each group described an elevated risk of psychosis in their community and explanations followed the following themes, with increased rates due to: (a) an accumulation of stressors due to disadvantaged ethnic minority status, (b) further disadvantage due to inequitable experiences of mental health services, (c) an absence of community support and (d) a double stigma: as a result of external discrimination, due to ethnicity, and internal stigma about mental illness from within the Black community itself. Conclusions: Black mental health service users attributed an elevated risk of psychosis in their community to an accumulation of stressors directly related to ethnic minority status.